Examining rumour mongering and counter-rumour conversation among Filipino youth in messenger - Pemmelaar, Charlotte P.; Opalia, Shane Louise L.; Amatosa, Samuel L.; Nacionales, Joseph P.; Claridad, Noberto (Journal of Language and Pragmatics Studies, 2023)
Messenger systems are one of the quickest ways to spread information, but they have also been used to disseminate false information. If unchecked, rumour - mongering can  have bad consequences. Counter-rumours, or assertions that refute them, are a powerful way to put an end to rumours. The rapid spread of rumours on websites like Messenger, in the opinion of Kucharski et al (2020), may cause people to feel anxious and apprehensive. With regards to the continued significance of messenger platforms in the lives of Filipino youth, there is an increasing need for research into how they emotionally process rumours and counter-rumours as well as how they come up with effective coping mechanisms. This study employed a qualitative approach through Interpretative Phenomenological Analysis and Braun and Clarke's thematic analysis. The 28 participants who were interviewed by the researchers were all Filipino youth who came from region VIII. The feelings and rumour-busting tactics employed by Filipino youth in Messenger were the findings that researchers gathered. Specifically, they experienced the unhappiness of the rumours, as well as how upsetting and discouraging they were, as well as their pain, guilt, and confusion. Be unbothered, keep quiet, ignore the rumours, avoid conflict, educate the populace, and make it clear that you are aware of the veracity of the rumours were the tactics they employed.